2018
DOI: 10.1088/1757-899x/316/1/012063
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic digestion of citrus waste using two-stage membrane bioreactor

Abstract: Abstract. Anaerobic digestion is a promising method to treat citrus waste. However, the presence of limonene in citrus waste inhibits anaerobic digestion process. Limonene is an antimicrobial compound and could inhibit methane forming bacteria that takes a longer time to recover than the injured acid forming bacteria. Hence, volatile fatty acids will be accumulated and methane production will be decreased. One way to solve this problem is by conducting anaerobic digestion process into two stages. The first ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Moreover, in comparison with the methane yield (0.30 Nm 3 /kg VS) obtained by Millati et al [ 20 ] who deployed a two-stage batch operation, the two-stage semi-continuous operation also exhibited an improved performance. The superiority of repeated batch operation might be due to the lower concentration of D-Limonene in the medium compared to that of batch operation.…”
Section: Resultsmentioning
confidence: 65%
“…Moreover, in comparison with the methane yield (0.30 Nm 3 /kg VS) obtained by Millati et al [ 20 ] who deployed a two-stage batch operation, the two-stage semi-continuous operation also exhibited an improved performance. The superiority of repeated batch operation might be due to the lower concentration of D-Limonene in the medium compared to that of batch operation.…”
Section: Resultsmentioning
confidence: 65%
“…The bactericidal properties are ascribed to D -limonene, present in essential oils [ 29 , 30 , 31 ]. D-Limonene in the peels is also known to cause issues in the anaerobic degradation during biogas [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the presence of the antibacterial compound D-Limonene, the peels of citrus fruits are less utilizable in biogas production. Studies have indicated that the D-Limonene present in citrus peels inhibits the anaerobic digestion of the waste by preventing the growth of bacterial colonies [ 3 , 4 ]. In addition, studies have also indicated that the extraction of the D-Limonene and other bactericidal compounds from the citrus peel enhances the anaerobic digestion and subsequent conversion of these waste products into biogas [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apesar do estudo da comunidade microbiana envolvida no processo de digestão anaeróbia ser essencial para a compreensão do comportamento dos reatores anaeróbios sob diferentes condições operacionais e como estas afetam as vias metabólicas predominantes e consequentemente os metabólitos obtidos, além de informações acerca da resistência a potenciais agentes tóxicos e/ou recalcitrantes, diversas pesquisas ainda se baseiam apenas em dados físico-químicos para avaliação dos resultados obtidos (DATAR et al, 2007;MILLATI et al, 2018). Entretanto, é fundamental a obtenção de dados físico-químicos e biológicos para melhor compreensão de diferentes configurações de reatores anaeróbios.…”
Section: Técnicas De Biologia Molecular Aplicadas Ao Estudo De Microrganismos Em Reatores Anaeróbiosunclassified